Efficient resource allocation in ad hoc grid: model, algorithm and simulation. (1st January 2011) - Chunlin, Li; Layuan, Li
Ad hoc grids are characterised by heterogeneity, autonomy, and volatility. This paper presents an efficient resource allocation in ad hoc grid. The resource allocation model makes use of two economic agent types: the ad hoc grid resource agents that represent the economic interests of the underlying resources of the ad hoc grid and the ad hoc grid task agents that represent the interests of ad hoc grid user using the grid to achieve goals. Ad hoc grid resource agent is used at the source node in the ad hoc grid and is deployed at the entry node. The ad hoc grid task agents buy resources to complete tasks. Ad hoc grid resource agents charge the task agents for the amount of resource capacity allocated. In the simulation, the performance evaluation of proposed algorithm for ad hoc grid is conducted.